Composite film strain sensor for battery bump monitoring and manufacturing method thereof
By designing a composite thin-film strain sensor, which incorporates different stresses and forms a Wheatstone bridge, the problem of early warning lag and lack of non-invasiveness in battery bulging monitoring is solved, enabling real-time and accurate monitoring of the battery interior. This technology is suitable for electric vehicles and energy storage systems.
Patent Information
- Application Number
- CN202511487075.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-17
- Publication Date
- 2026-01-09
AI Technical Summary
Existing battery bulging monitoring technologies suffer from problems such as delayed early warning, insufficient non-invasiveness, slow response speed, low accuracy, and non-in-situ monitoring. Traditional implantable sensors can damage battery sealing and shorten lifespan, and are also susceptible to corrosion and oxidation.
A composite thin-film strain sensor is designed, comprising a current collector, an isolation layer, a strain layer support, a protective layer, a composite strain-sensitive layer, and an electrode connection layer. The composite strain-sensitive layer is constructed using magnetron sputtering and photolithography processes, incorporating different stresses to achieve directional curling and forming a Wheatstone bridge, suitable for non-destructive implantation inside batteries.
It enables real-time in-situ monitoring of battery bulging, improves response speed and monitoring accuracy, avoids damage to battery sealing caused by traditional sensors, and is suitable for full life cycle monitoring of electric vehicles and energy storage systems.
Smart Images

Figure CN121297648A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of thin-film sensor technology, and relates to a composite thin-film strain sensor for monitoring battery bulging and its fabrication method. Background Technology
[0002] In critical fields such as electric vehicles and energy storage systems, lithium-ion batteries serve as the core power source, and their safety and reliability directly affect the stable operation of the entire system and the safety of users' lives and property. Battery bulging is a typical external manifestation of internal mechanical failure in lithium-ion batteries. Its causes are complex and diverse, mainly including lithium intercalation expansion of electrode materials, thermal effects caused by internal short circuits, and structural stress concentration. According to authoritative statistics, there were more than 9,486 lithium battery safety incidents worldwide between 2020 and 2024, a significant number of which were closely related to battery bulging. Bulges can trigger a series of serious problems, such as electrode breakage and electrolyte leakage, thereby threatening the normal use and safety of the battery. Crucially, if battery bulging is not detected in its early stages, it can rapidly develop into thermal runaway within just 10-15 minutes, ultimately leading to catastrophic consequences such as battery spontaneous combustion and explosion, causing irreparable damage.
[0003] Currently, existing battery bulging monitoring technologies mainly rely on surface temperature sensors and pressure sensors. However, these technologies have significant limitations. In the early stages of bulging, the internal strain of the battery exhibits significant non-uniformity, while surface signals often lag behind the actual changes inside the battery. This results in surface signals failing to accurately reflect the internal deformation state of the battery in real time, significantly reducing the timeliness and accuracy of early warnings. Traditional implantable sensors, such as fiber Bragg gratings, can acquire information about the battery's internal structure to some extent, but face numerous challenges in practical applications. Installing these sensors requires drilling through the battery casing, which severely compromises the battery's seal and significantly increases the risk of electrolyte leakage. Moreover, their thickness far exceeds that of the electrode film, causing localized stress concentration after implantation, accelerating battery aging and shortening its lifespan. Furthermore, the electrolyte inside the battery has a corrosive and oxidizing effect on metal or semiconductor sensors. If the sensor is not properly sealed, its performance will significantly drift after immersion in the electrolyte, failing to meet the monitoring requirements throughout the battery's entire lifespan.
[0004] In summary, existing technologies for battery bulging monitoring suffer from numerous drawbacks, including delayed early warning, insufficient non-invasiveness, slow response speed, low accuracy, and non-in-situ monitoring. Therefore, developing a strain sensor that can be non-destructively implanted inside the battery is urgently needed. The successful development of such a sensor will provide crucial hardware support for next-generation smart battery safety warning systems, significantly promoting a comprehensive upgrade in reliability for electric vehicles and energy storage. Summary of the Invention
[0005] In view of this, the purpose of the present invention is to provide a composite thin-film strain sensor for monitoring battery bulging and a method for manufacturing the same, so as to solve the problem that the prior art is difficult to achieve rapid, non-destructive, real-time in-situ monitoring of lithium battery bulging.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] A composite thin-film strain sensor for monitoring battery bulging includes, from bottom to top, a current collector, an isolation layer, a strain layer support, a first protective layer, a composite strain-sensitive layer, and a second protective layer, and an electrode connection layer disposed between the first and second protective layers for electrically connecting the composite strain-sensitive layer.
[0008] The composite strain-sensitive layer includes a first strain layer and a second strain layer. The first strain layer and the second strain layer have different internal stresses to achieve directional curling of the composite strain-sensitive layer and convert the internal deformation of the battery into a change in resistance, which is output through the electrode connection layer to achieve in-situ monitoring of battery bulging.
[0009] Furthermore, the isolation layer comprises a TiNiCu shape memory alloy layer and an insulating layer arranged sequentially from bottom to top. The atomic percentage of the TiNiCu shape memory alloy layer is Ti:Ni:Cu = 49:47:4, and the thickness is 1-2 μm. The insulating layer is Al2O3 with a thickness of 500 nm.
[0010] Furthermore, the TiNiCu shape memory alloy layer is deposited using a magnetron sputtering process, with process parameters including a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas flow rate 25 sccm, sputtering power 120 W, deposition rate approximately The shape memory properties are obtained by vacuum annealing at 580℃ for 0.5h.
[0011] Furthermore, the strain layer support is a polyimide square boss with dimensions of 10mm×10mm and a height of 10-50μm.
[0012] Furthermore, the composite strain-sensitive layer comprises 4-20 strip-shaped sensitive grids arranged in an array, with a grid spacing of 10-400 μm, a grid length of 1-5 mm, and a grid width of 10-200 μm.
[0013] Furthermore, the electrode connection layer is made of Au material with a thickness of 100 nm; the first protective layer and the second protective layer are made of polyimide material with a thickness of 2-20 μm.
[0014] Furthermore, the first strain layer is made of Cr material with a thickness of 50-100 nm and contains a tensile stress σ1.
[0015] The second strain layer is made of CuNi material with a thickness of 100-500 nm, and has an internal compressive stress σ2. The mass ratio of Cu to Ni is 55:45.
[0016] The thickness ratio of the first strain layer to the second strain layer is between 1:2 and 1:5.
[0017] Furthermore, the deposition process parameters for the first strain layer are a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas pressure 1.0 Pa, Ar gas flow rate 20 sccm, sputtering power 100 W, deposition rate approximately Substrate temperature 50℃;
[0018] The deposition process parameters for the second strain layer are a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas pressure 3.0 Pa, Ar gas flow rate 20 sccm, sputtering power 150 W, deposition rate approximately The substrate temperature is 20℃.
[0019] Furthermore, the bending curvature of the composite strain-sensitive layer is:
[0020]
[0021] Where t1 and t2 are the thicknesses of the lower and upper thin films in the composite strain-sensitive layer, respectively; E1 and E2 are the Young's moduli of the lower and upper thin films in the composite strain-sensitive layer, respectively.
[0022] Furthermore, the micro-nano composite thin film strain sensor adopts an "H"-shaped centrally symmetrical arrangement, including two upward bending strain modules and two downward bending strain modules. Each of the upward bending strain modules and the two downward bending strain modules includes a composite strain sensitive layer and a first protective layer and a second protective layer disposed on both sides of the composite strain sensitive layer.
[0023] The upward bending strain module and the downward bending strain module form a Wheatstone bridge, which is used to counteract environmental interference and improve monitoring accuracy.
[0024] In the composite strain-sensitive layer at the upward bending strain module, the first strain layer is the upper thin film, and the second strain layer is the lower thin film.
[0025] In the composite strain-sensitive layer at the downward bending strain module, the second strain layer is the upper thin film, and the first strain layer is the lower thin film.
[0026] On the other hand, the present invention also provides a method for manufacturing a composite thin-film strain sensor for monitoring battery bulging, applied to the composite thin-film strain sensor, characterized by comprising the following steps:
[0027] S1: Clean the hard substrate, apply the heat release tape to the hard substrate, and then apply the current collector to the heat release tape;
[0028] S2: A patterned isolation layer is fabricated on the current collector using photolithography, lift-off process and magnetron sputtering process;
[0029] S3: A strain layer support is formed on the isolation layer using photolithography.
[0030] S4: Spin-coat negative photoresist in the area not covered by the strain layer support on the isolation layer to form a sacrificial layer;
[0031] S5: A first protective layer is formed on the strained layer support and the sacrificial layer using photolithography.
[0032] S6: A composite strain-sensitive layer at the downward bending strain module is prepared on the first protective layer using photolithography, lift-off process and magnetron sputtering process, including a patterned first strain layer and second strain layer;
[0033] By changing the deposition sequence, a composite strain-sensitive layer of upwardly bent strain module is prepared on the first protective layer, including a patterned second strain layer and a first strain layer;
[0034] S7: A patterned electrode connection layer is fabricated on the first protective layer using photolithography, lift-off process and magnetron sputtering process;
[0035] S8: A second protective layer is formed on the composite strain-sensitive layer and the electrode connection layer using photolithography.
[0036] S9: Dissolve the sacrificial layer to release the composite strain-sensitive layer, causing it to curl in an orientation; heat release the thermal release tape to obtain a micro-nano composite thin film strain sensor.
[0037] Furthermore, the method includes encapsulating the micro / nano composite thin film strain sensor with a battery electrode material layer using a battery encapsulation process to obtain a battery in which the composite thin film strain sensor is internally implanted.
[0038] The beneficial effects of this invention are as follows:
[0039] 1. The micro / nano composite thin-film strain sensor of this invention addresses the pain point of monitoring lithium-ion battery bulging by providing an implantable solution capable of real-time, in-situ monitoring of internal battery deformation. This sensor is directly fabricated on the battery current collector and includes structures such as an isolation layer, a strain layer support, a protective layer, a composite strain-sensitive layer, and an electrode connection layer. The composite strain-sensitive layer is constructed using magnetron sputtering and photolithography. This layer incorporates different stresses (such as the tensile stress of the Cr layer and the compressive stress of the CuNi layer) to achieve directional curling and form a Wheatstone bridge circuit. This design is compatible with battery packaging processes, allowing for non-destructive implantation without compromising battery sealing. It avoids the drilling risks and stress concentration problems associated with fiber Bragg gratings, thus having virtually no impact on battery performance.
[0040] 2. The isolation layer uses a TiNiCu shape memory alloy (atomic ratio Ti:Ni:Cu = 49:47:4) and an Al2O3 insulating layer, exhibiting shape memory properties. After dynamic deformation caused by battery charging and discharging, the initial strain state can be restored by external heating, reducing error accumulation. Simultaneously, the sensor employs an "H"-shaped, centrally symmetrical arrangement of two upward-bending and two downward-bending strain modules, forming a Wheatstone bridge, which effectively counteracts environmental interference such as temperature or vibration effects, improving response sensitivity and monitoring accuracy. The composite strain-sensitive layer array design (4-20 strip-shaped sensitive grids) further enhances flexibility and accuracy, with a grid spacing of 10-400 μm and a grid width of 10-200 μm, ensuring rapid response to minute deformations, far superior to the signal hysteresis limitations of surface sensors.
[0041] 3. In summary, this invention significantly improves battery safety early warning capabilities, offering fast response, high accuracy, and good flexibility, making it suitable for electric vehicles and energy storage systems. Compared to existing technologies, it reduces signal delay and distortion, supports full lifecycle monitoring, and promotes the reliability upgrade of smart batteries.
[0042] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0043] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0044] Figure 1 This is a schematic diagram of the structure of a micro / nano composite thin film strain sensor for monitoring battery bulging in Example 1;
[0045] Figure 2This is a cross-sectional schematic diagram of a micro / nano composite thin film strain sensor used for monitoring battery bulging, as shown in Example 1.
[0046] Reference numerals in the attached figures: 1-current collector; 2-isolation layer; 3-strain layer support; 4-first protective layer; 5-first strain layer; 6-second strain layer; 7-electrode connection layer; 8-second protective layer. Detailed Implementation
[0047] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0048] The accompanying drawings are for illustrative purposes only and are schematic diagrams, not actual pictures. They should not be construed as limiting the invention. To better illustrate the embodiments of the invention, some parts in the drawings may be omitted, enlarged, or reduced, and do not represent the actual product dimensions. It is understandable to those skilled in the art that some well-known structures and their descriptions may be omitted in the drawings.
[0049] In the accompanying drawings of the embodiments of the present invention, the same or similar reference numerals correspond to the same or similar components. In the description of the present invention, it should be understood that if terms such as "upper," "lower," "left," "right," "front," and "rear" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the drawings, they are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, the terms used to describe positional relationships in the drawings are only for illustrative purposes and should not be construed as limiting the present invention. For those skilled in the art, the specific meaning of the above terms can be understood according to the specific circumstances.
[0050] Example 1
[0051] See Figure 1 and Figure 2 A micro / nano composite thin film strain sensor for monitoring battery bulging includes a current collector 1, an isolation layer 2, a strain layer support 3, a first protective layer 4, a first strain layer 5, a second strain layer 6, an electrode connection layer 7, and a second protective layer 8.
[0052] The isolation layer 2 consists of a TiNiCu shape memory alloy layer and an Al3O2 layer from bottom to top, both deposited by magnetron sputtering.
[0053] The TiNiCu shape memory alloy layer has a film thickness of 2 μm and an atomic percentage of Ti:Ni:Cu of 49:47:4; the Al3O2 layer has a thickness of 500 nm and serves as an insulating layer.
[0054] The strain layer support 3 is a 10mm×10mm polyimide square boss with a height of 30μm.
[0055] The first strain layer 5 and the second strain layer 6 constitute a composite strain sensitive layer. The composite strain sensitive layer includes eight strip sensitive grids arranged in an array, with a grid spacing of 100 μm, a grid length of 3 mm, and a grid width of 50 μm.
[0056] The thickness ratio of the first strain layer 5 to the second strain layer 6 is 1:4.
[0057] The strain material of the first strain layer 5 is Cr, the film thickness is 100nm, and it has built-in tensile stress; the strain material of the second strain layer 6 is CuNi, the film thickness is 400nm, and it has built-in compressive stress, wherein the mass ratio of Cu to Ni is 55:45.
[0058] The micro-nano composite thin film strain sensor is arranged in an "H" shaped central symmetric arrangement, including two upward bending strain modules and two downward bending strain modules. Each of the upward bending strain modules and the two downward bending strain modules includes a composite strain sensitive layer and a first protective layer 4 and a second protective layer 8 disposed on both sides of the composite strain sensitive layer.
[0059] The upward bending strain module and the downward bending strain module form a Wheatstone bridge, which is used to counteract environmental interference and improve monitoring accuracy.
[0060] In the composite strain sensitive layer at the upward bending strain module, the first strain layer 5 is the upper thin film, and the second strain layer is the lower thin film.
[0061] In the composite strain-sensitive layer at the downward bending strain module, the second strain layer 6 is the upper thin film, and the first strain layer 5 is the lower thin film.
[0062] The electrode connection layer 7 is made of Au and has a thickness of 100 nm.
[0063] The first protective layer 4 and the second protective layer 8 are both polyimide with a thickness of 10 μm.
[0064] The working principle of the micro / nano composite thin film strain sensor for monitoring battery bulging provided in this embodiment is as follows:
[0065] The micro-nano composite thin film strain sensor obtains strain modules with directional curling amplitude by embedding different stresses in each layer of the composite strain sensitive layer, and forms a Wheatstone bridge. When the battery bulges, it changes the curling degree of the strain module, causing a change in the resistance of the strain module, thereby realizing in-situ monitoring of battery bulge.
[0066] Example 2
[0067] This embodiment provides a method for fabricating a micro / nano composite thin film strain sensor for monitoring battery bulging, which is applied to the micro / nano composite thin film strain sensor and includes the following specific steps:
[0068] S1: Clean the hard substrate, apply the heat release tape flatly to the hard substrate, then align the current collector 1 and apply it to the heat release tape, apply uniform pressure with a roller to ensure a tight seal without air bubbles;
[0069] S2: A patterned isolation layer 2 is fabricated on current collector 1 using photolithography, lift-off, and magnetron sputtering processes. After vacuum annealing of the TiNiCu layer, heat release tape is reattached. The TiNiCu shape memory alloy layer has a thickness of 2 μm, and the Al3O2 layer has a thickness of 500 nm. The deposition process parameters for the TiNiCu shape memory alloy layer are a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas flow rate 25 sccm, sputtering power 120 W, deposition rate approximately Vacuum annealing at 580℃ for 0.5h yields good shape memory properties.
[0070] S3: A strain layer support 3 is formed on the isolation layer 2 using photolithography, forming a polyimide square boss with a height of 30μm;
[0071] S4: Spin-coat negative photoresist onto the isolation layer 2 with strain layer support 3, and after pre-baking exposure patterning, hard film is formed to form a sacrificial layer with a film thickness of 50μm.
[0072] S5: A first protective layer 4 of polyimide is formed on the sacrificial layer using photolithography, with a film thickness of 10μm;
[0073] S6: Patterned first strain layer 5 and second strain layer 6 are fabricated on the first protective layer 4 using photolithography, lift-off process and magnetron sputtering process respectively as a downward bending strain module. The first strain layer 5 has a Cr film thickness of 100nm and the second strain layer 6 has a CuNi film thickness of 400nm.
[0074] S7: Change the deposition order of the first strain layer 5 and the second strain layer 6, and use photolithography, lift-off process and magnetron sputtering process to prepare patterned second strain layer 6 and first strain layer 5 on the first protective layer 4 as strain modules that bend upward. The thickness of the first strain layer 5 Cr film is 100nm and the thickness of the second strain layer 6 CuNi film is 400nm.
[0075] The deposition process parameters for the first strain layer 5 are a vacuum degree of 1×10⁵. -5 Pa, Ar gas pressure 1.0 Pa, Ar gas flow rate 20 sccm, sputtering power 100 W, deposition rate approximately Substrate temperature 50℃, with built-in tensile stress σ1;
[0076] The deposition process parameters for the second strain layer 6 are a vacuum degree of 1×10⁶. -5 Pa, Ar gas pressure 3.0 Pa, Ar gas flow rate 20 sccm, sputtering power 150 W, deposition rate approximately Substrate temperature 20℃, with built-in compressive stress σ2;
[0077] S8: A patterned electrode connection layer 7 with a thickness of 100 nm was fabricated on the composite strain-sensitive layer using photolithography, lift-off process and magnetron sputtering process.
[0078] S9: A second protective layer 8 of polyimide is formed on the composite strain-sensitive layer using photolithography, with a film thickness of 2-20μm;
[0079] S10: Dissolve the sacrificial layer using a desiccant to release the composite strain-sensitive layer, which then curls in an oriented manner. After being heated by a hot plate, the current collector 1 is released by the heat-release tape, thus obtaining a micro / nano composite thin film strain sensor.
[0080] Furthermore, the micro-nano composite thin film strain sensor is encapsulated with the battery electrode material layer using a battery encapsulation process to obtain a battery with an internally implanted micro-nano composite thin film strain sensor.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A composite thin-film strain sensor for monitoring battery bulging, characterized in that, It includes, from bottom to top, a current collector (1), an isolation layer (2), a strain layer support (3), a first protective layer (4), a composite strain sensitive layer and a second protective layer (8), and an electrode connection layer (7) disposed between the first protective layer (4) and the second protective layer (8) for electrically connecting the composite strain sensitive layer; The composite strain-sensitive layer includes a first strain layer (5) and a second strain layer (6). The first strain layer (5) and the second strain layer (6) have different internal stresses to achieve directional curling of the composite strain-sensitive layer and convert the internal deformation of the battery into a change in resistance, which is output through the electrode connection layer (7) to achieve in-situ monitoring of battery bulging.
2. The composite thin-film strain sensor according to claim 1, characterized in that, The isolation layer (2) includes a TiNiCu shape memory alloy layer and an insulating layer arranged sequentially from bottom to top. The atomic percentage of the TiNiCu shape memory alloy layer is Ti:Ni:Cu = 49:47:4, and the thickness is 1-2μm. The insulating layer is Al2O3 with a thickness of 500nm.
3. The composite thin-film strain sensor according to claim 2, characterized in that, The TiNiCu shape memory alloy layer was deposited using a magnetron sputtering process, with process parameters including a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas flow rate 25 sccm, sputtering power 120 W, deposition rate approximately The shape memory properties are obtained by vacuum annealing at 580℃ for 0.5h.
4. The composite thin-film strain sensor according to claim 1, characterized in that, The strain layer support (3) is a polyimide square boss with a size of 10mm×10mm and a height of 10-50μm.
5. The composite thin-film strain sensor according to claim 1, characterized in that, The composite strain-sensitive layer comprises 4-20 strip-shaped sensitive grids arranged in an array, with a grid spacing of 10-400 μm, a grid length of 1-5 mm, and a grid width of 10-200 μm.
6. The composite thin-film strain sensor according to any one of claims 1 to 5, characterized in that, The first strain layer (5) is made of Cr material with a thickness of 50-100nm and contains a tensile stress σ1. The second strain layer (6) is made of CuNi material with a thickness of 100-500nm, and has a built-in compressive stress σ2. The mass ratio of Cu to Ni is 55:
45. The thickness ratio of the first strain layer (5) and the second strain layer (6) is between 1:2 and 1:
5.
7. The composite thin-film strain sensor according to claim 6, characterized in that, The deposition process parameters for the first strain layer (5) are a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas pressure 1.0 Pa, Ar gas flow rate 20 sccm, sputtering power 100 W, deposition rate approximately Substrate temperature 50℃; The deposition process parameters for the second strain layer (6) are a vacuum degree of 1×10⁻⁶. -5 Pa, Ar gas pressure 3.0 Pa, Ar gas flow rate 20 sccm, sputtering power 150 W, deposition rate approximately The substrate temperature is 20℃.
8. The composite thin-film strain sensor according to claim 6, characterized in that, The bending curvature of the composite strain-sensitive layer is: Where t1 and t2 are the thicknesses of the lower and upper thin films in the composite strain-sensitive layer, respectively; E1 and E2 are the Young's moduli of the lower and upper thin films in the composite strain-sensitive layer, respectively.
9. The composite thin-film strain sensor according to claim 6, characterized in that, The micro-nano composite thin film strain sensor adopts an "H"-shaped central symmetrical arrangement, including two upward bending strain modules and two downward bending strain modules. The upward bending strain module and the two downward bending strain modules each include a composite strain sensitive layer and a first protective layer (4) and a second protective layer (8) disposed on both sides of the composite strain sensitive layer. The upward bending strain module and the downward bending strain module form a Wheatstone bridge, which is used to counteract environmental interference and improve monitoring accuracy. In the composite strain sensitive layer at the upward bending strain module, the first strain layer (5) is the upper thin film, and the second strain layer (6) is the lower thin film. In the composite strain sensitive layer at the downward bending strain module, the second strain layer (6) is the upper thin film, and the first strain layer (5) is the lower thin film.
10. A method for fabricating a composite thin-film strain sensor for monitoring battery bulging, applied to the composite thin-film strain sensor described in claim 9, characterized in that, Includes the following steps: S1: Clean the hard substrate, attach the heat release tape to the hard substrate, and then attach the current collector (1) to the heat release tape; S2: A patterned isolation layer (2) is prepared on the current collector (1) using photolithography, lift-off process and magnetron sputtering process; S3: A strain layer support (3) is formed on the isolation layer (2) using photolithography. S4: Spin-coat negative photoresist on the area not covered by the strain layer support (3) on the isolation layer (2) to form a sacrificial layer; S5: A first protective layer (4) is formed on the strain layer support (3) and the sacrificial layer using photolithography; S6: A composite strain-sensitive layer at the downward bending strain module is prepared on the first protective layer (4) using photolithography, lift-off process and magnetron sputtering process, including a patterned first strain layer (5) and second strain layer (6); By changing the deposition sequence, a composite strain-sensitive layer of upward bending strain module is prepared on the first protective layer (4), including a patterned second strain layer (6) and a first strain layer (5); S7: A patterned electrode connection layer (7) is prepared on the first protective layer (4) using photolithography, lift-off process and magnetron sputtering process; S8: A second protective layer (8) is formed on the composite strain-sensitive layer and electrode connection layer (7) using photolithography. S9: Dissolve the sacrificial layer to release the composite strain-sensitive layer, causing it to curl in an orientation; Heating releases the thermal release tape, resulting in a micro / nano composite thin film strain sensor.
